Strengthening Scientific Integrity: Digital Forensics for Biomedical Research Imaging - Cardenuto, João Phillipe; Moreira, Daniel; Rocha, Anderson (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2025.38268, 2025)
To combat the increasing number of misconduct cases in science, this Ph.D. research addressed the challenge of scientific integrity with a pioneering investigation into digital forensic analysis specifically tailored for biomedical research imaging. This work conducted extensive research into key manipulation types—copy-move forgery, image reuse, and AI-generated content—developing novel, fully explainable, and auditable computational detection methods for each. In a commitment to transparency and to promote research in the area, these techniques are provided as open-source resources. Besides the isolated techniques for each type of image forged, a central contribution is the development of an end-to-end system, created through collaboration with international forensic experts and the U.S. Office of Research Integrity (ORI). This system automates the analysis of scientific publications, starting from PDF documents and ending by identifying figures with potential integrity concerns.